2021
DOI: 10.1007/s12187-021-09853-w
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Developmental Contexts in Adolescent’s Expected Sociopolitical Participation through the Sense of Unity: An Analysis of the Mediation Model Invariance through Sex, Age, and Socioeconomic Status

Abstract: Civic engagement plays a positive role in adolescent wellbeing, as well as being the basis for maintaining a democratic society. This research analyzed how perceived support from developmental contexts contributes to adolescent civic engagement –assessed through their expectations of future sociopolitical participation–, mediated by sense of unity, and differences according to sex, age, and socioeconomic status. The sample included 3,715 participants (13–18 years old) from the 2019 OPINA Barometer who were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
1
1
0
1
Order By: Relevance
“…Once obtaining results on the scale’s reliability and validity in Spanish and Portuguese adolescents, mean scores of both groups were examined, taking into consideration sex, age, and country. Results showed that Spanish adolescents score higher than Portuguese, coinciding with research by Salado et al (2023). However, we must be cautious when interpreting these results given that there is a noticeable lack of prior research comparing the social self-efficacy scale in both countries.…”
Section: Discussionsupporting
confidence: 61%
“…Once obtaining results on the scale’s reliability and validity in Spanish and Portuguese adolescents, mean scores of both groups were examined, taking into consideration sex, age, and country. Results showed that Spanish adolescents score higher than Portuguese, coinciding with research by Salado et al (2023). However, we must be cautious when interpreting these results given that there is a noticeable lack of prior research comparing the social self-efficacy scale in both countries.…”
Section: Discussionsupporting
confidence: 61%
“…En este sentido, adaptan la creencia de que la política está más asociada al género masculino aumentando aún más la brecha de género en las facetas de socialización política (Arens & Watermann, 2017). En cuanto a las puntuaciones en las expectativas de las chicas sobre su participación futura en asuntos sociopolíticos, está también constatada por estudios previos (Gaby, 2017;Salado et al,2021). Creemos que, debido a que los ítems de la escala utilizada miden en mayor medida asuntos de índole social, se puede afirmar que puede existir un mayor compromiso social de las chicas a diferencia de un mayor compromiso político en los chicos (Cicognani et al, 2012; Wray-Lake & Shubert, 2019).…”
Section: Discussionunclassified
“…Thus, parents tend to foster caregiving values and concern for others to a higher degree in girls than in boys (Wray-Lake et al, 2012). This causes girls to have more social concerns, help others, and participate in activities such as volunteering (Gaby, 2017), or have future expectation of participating in social issues (Salado et al, 2022), whereas boys’ interests are more related to political issues such as the intention of voting in the future or following news on different media platforms (Wray-Lake et al, 2020). Moreover, gender differences have also been found in adolescents’ concerns with social issues, with girls showing more concerns for issues like racism, hunger, poverty, and crime and violence compared to their male peers (Oosterhoff et al, 2020).…”
Section: Introductionmentioning
confidence: 99%